View of the rear elevation of the southern shrine - Temples of India Project Team (Jio Institute, 2024)
This is the view of the rear elevation of the southern shrine of the triple-shrine Neelkanth Mahadev Temple. The exterior walls of this shrine have completely collapsed and were replaced at a later point with incongruously added wall portions. In rebuilding these walls, architectural members of the original temple have been repurposed haphazardly.